Novel MEIS1-NCOA2 Gene Fusions Define a Distinct Primitive Spindle Cell Sarcoma of the Kidney. (November 2018) - Argani, Pedram; Reuter, Victor E.; Kapur, Payal; Brown, James E.; Sung, Yun-Shao; Zhang, Lei; Williamson, Richard; Francis, Glen; Sommerville, Scott; Swanson, David; Dickson, Brendan C.; Antonescu, Cristina R.
Abstract : We describe 2 cases of a distinct sarcoma characterized by a novel MEIS1-NCOA2 gene fusion. This gene fusion was identified in the renal neoplasms of 2 adults (21-y-old male, 72-y-old female). Histologically, the resected renal neoplasms had a distinctively nodular appearance, and while one renal neoplasm was predominantly cystic, the other demonstrated solid architecture, invasion of perirenal fat, and renal sinus vasculature invasion. The neoplasms were characterized predominantly by monomorphic plump spindle cells arranged in vague fascicles with a whorling pattern; however, a more primitive small round cell component was also noted. Both neoplasms were mitotically active and one case showed necrosis. The neoplasms did not have a distinctive immunohistochemical profile, though both labeled for TLE1. The morphologic features are distinct from other sarcomas associated with NCOA2 gene fusions, including mesenchymal chondrosarcoma, congenital/infantile spindle cell rhabdomyosarcoma, and soft tissue angiofibroma. While we have minimal clinical follow-up, the aggressive histologic features of these neoplasms indicate malignant potential, thus warranting classification as a novel subtype of sarcoma. Abstract : Supplemental Digital Content is available in the text.